PENGARUH IMPLEMENTASI PROGRAM KAMPUNG RESIK LAN AMAN TERHADAP PENINGKATAN KESADARAN LINGKUNGAN BERSIH DAN AMAN DI KOTA SERANG - Masyruroh, Anis; Rahmawati, Iroh (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2022)
The Resik lan Aman village program is the flagship program of the Serang City Government, with the aim of providing awareness to the people of Serang City, so that they can create a clean and safe environment, so that the habits and behavior of littering in the Serang City community can change. The research objectives were used to answer the following questions: 1) How much influence does the implementation of the clean and safe village program have on increasing awareness of a clean environment, 2 What is the impact of the implementation of the clean and safe village program on improving environmental conditions in Serang City. This research method uses a quantitative approach. Data collection techniques were carried out through questionnaires to obtain data. The data analysis was carried out using multiple linear regression to see how much contribution was given by the Kampung Resik lan Aman program of Serang City to the awareness of the people of Serang City in terms of cleanliness and environmental safety. The results of this study indicate The implementation of the Kampung Resik lan Aman program of Serang City has an effect on increasing awareness of a clean and safe environment by 0.765 or 76.5% and has an impact on the reduction of slum areas in Serang City.